Movements, space use, and vital rates of mourning doves - Pegg, Natalie Frances (My University, 2026)
The mourning dove (Zenaida macroura) is an important North American gamebird, yet contemporary demographic information needed to guide management remains limited at the spatial scales where management occurs. In Kansas, USA, mourning doves occupy landscapes that vary substantially in climate, vegetation, urbanization, and management intensity, providing an opportunity to evaluate how demographic rates change across broad ecological and land-use gradients. My goal was to quantify variation in movements, space use, and vital rates of mourning doves in Kansas to improve understanding of the processes shaping recruitment and population dynamics. First, I estimated egg- and nestling-stage daily survival, period survival, and nest-site selection during 2023–2025 across 4 study locations representing 3 BCRs and urban, rural, and wildlife management area treatments. Egg-stage survival varied across location and treatment, with egg-stage period survival lowest in rural treatments (0.28, 95% CI = 0.09–0.82) compared to urban (0.76, 95% CI = 0.71–0.81) and wildlife management areas (0.71, 95% CI = 0.61–0.83). In contrast, nestling-stage survival varied primarily by year and was greatest in 2024 (0.99, 95% CI = 0.98–0.99). Mourning doves selected trees with larger diameters than available trees, but tree species selection was generally weak and ground-nest selection showed little relationship with measured cover variables. Together, these findings suggest that egg and nestling stages may be influenced by different processes and that selected nest-site features do not necessarily correspond to greater survival. Second, I quantified space use, land-cover associations, and weekly apparent survival of after-hatch-year mourning doves fitted with radio transmitters during 2023–2025. I marked 396 individuals, relocated 112 at least once, and recorded 431 detections. Among individuals with more than 20 detections, average 95% home range area was 70.83 ± 97.83 ha and average 50% core area was 16.30 ± 25.60 ha, although variation among individuals was considerable. Across all detections, urban low-intensity and urban high-intensity land cover accounted for the largest proportions of observations (25.55% and 14.32%, respectively), though dominant land-cover classes differed among locations. Cormack-Jolly-Seber models supported location-specific differences in weekly apparent survival and detection probability, with weekly apparent survival ranging from 0.55 ± 0.13 to 0.93 ± 0.02 and detection probability ranging from 0.07 ± 0.02 to 0.50 ± 0.04. Finally, I evaluated statewide variation in annual survival and recovery rates of mourning doves banded in Kansas from 2003–2023 using dead recovery models. Survival and recovery varied across Bird Conservation Regions (BCR), land-use contexts, and age classes. This gradient was strongest for hatch-year birds, with annual survival declining from 0.52 ± 0.05 in BCR 18 to 0.31 ± 0.02 in BCR 22, whereas after-hatch-year survival varied less among BCRs. Mourning doves banded in urban areas had lower survival and greater recovery than birds banded in rural areas, and hatch-year birds banded in urban areas showed 51% lower survival and 40% greater recovery than those banded in rural areas. These results indicate substantial within-state heterogeneity in demographic rates and suggest that banding design and landscape context can influence inference. Collectively, this dissertation demonstrates that mourning dove demographic rates and space use vary substantially across Kansas and across life stages, land-use contexts, and regions. These results provide an important field-based foundation for interpreting broader population trends and suggest that locally informed, spatially explicit management will be necessary to effectively conserve and manage this widely harvested species.
Keywords: Wildlife; Movement; Management; Reproduction